Pembuktian Tindak Pidana Penganiayaan Berat Dengan Rencana sebagai Unsur Kealpaan; Analisis Putusan Nomor: 372/Pid.B/2020/PN.Jkt.Utr. - Wahyu Istiham Susanto (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This research explains the evidence regarding the element of error in the form of deliberate and accidental Mens Rea in the indictment, resulting in a mismatch with the existing Actus Reus and causing the element of error in the form of deliberation to become an element of negligence. This study aims to determine the cause of Primair's indication not being fulfilled based on the elements of the defendant's guilt in Case Decision Number: 372 / Pid.B / 2020 / PN.Jkt.Utr. In particular, this research examines the application of the doctrine of deliberate error in the Decision on Case Number: 372 / Pid.B / 2020 / PN.Jkt.Utr. In addition, this study also discusses the application of elements of criminal evidence. The research method used is a normative-doctrinal approach by looking for the correct answer by proving the truth of the legal prescription written in the Criminal Code through a statutory approach and a conceptual approach. The results showed that the primair indictment could not be proven because there was a material failure in the legal element of proof that this occurred at the time of the accident implementation in the form of deliberate action that was not in accordance with the legal facts contained in the trial with the charges and indictments. The formulation of errors used in the Decision on Case Number: 372 / Pid. B / 2020 / PN.Jkt.Utr. and is seen as the basis for determining